A Study on Learning Experiences through Wordwall Games: Affecting Development of Core Competencies and Quality in Early Childhood Learners - ลุงคำ, ญามินทร์; ลอยดู, พิราอร; เทศปลื้ม, มาริษา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) compare the basic scientific process skills of early childhood students before and after experiencing learning activities through the Wordwall game and 2) examine the collaborative behaviors of early childhood students before and after experiencing learning activities through the Wordwall game. The sample group consisted of 25 early childhood students from Kindergarten Levels 1 to 3 in Daniel Class at Mahachai Christian Wittaya School, selected through cluster random sampling. The research instruments included 1) a lesson plan designed to enhance scientific skills through games, 2) a scientific process skills test, and 3) an observation form for collaborative behavior. Data were analyzed using mean, standard deviation, and t-test for dependent samples.          The research findings revealed that: 1) Early childhood students who participated in learning activities through the Wordwall game demonstrated significantly higher basic scientific process skills after the activities than before, at a significance level of .05, and 2) Early childhood students exhibited improved collaborative behavior after the activities ( Mean = 2.82, S.D. = 0.19), which was categorized as good, compared to their behavior before the activities ( Mean = 2.46, S.D. = 0.25), which was categorized as fair.